The Chinese impact on GDP growth and inflation in the industrial countries - Christian Dreger; Yanqun Zhang (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
The integration of China into the global economy is one of the most spectacular events in economic history. This paper investigates to what extent this process affects output growth and inflation in the advanced countries. A GVAR model is specified to explore interdependencies between business cycles in China and industrial countries, including the US, the euro area and Japan. For robustness, the results are compared to those obtained from leading structural models, such as NiGEM and OEF. Evidence is based on the responses to a Chinese demand shock arising from the recent fiscal stimulus program. The results show that the impact on output growth in the advanced economies can be quite substantial, especially for the Asian region. The expansionary effects in the US and the euro area responses are lower, as trade linkages are less intensive. The multipliers are also reduced by a sizeable effect on inflation, as Chinese firms participate in international production chains.
Keywords: E32; F15; C51; 330; GVAR; Chinese economy; shock transmission; Wirtschaftswachstum; Konjunktur; Inflation; Schock; China; Konjunkturzusammenhang; Makroökonomischer Einfluss; USA; Eurozone; Japan; Asien